Improving The Quality Of Self-Organizing Map By “Different Elements" Competitive Strategy / Le Anh Tu - Le Anh Tu
In this paper, a method to improve the quality of the map obtained when the SOM'slearning algorithm ended is proposed. The proposed method re-adjusts weight vector of each neuronaccording to cluster's center that neuron represents and optimizes clusters by "diﬂerent elements“competitive strategy